Identifikasi Spesies Lalat Buah (Diptera: Tephritidae) pada Tanaman Cabai, Jambu Biji, dan Pare di Kabupaten Ogan Ilir, Sumatera Selatan - Nabil, Haidar; Wardhani, Annisa; Al Ghifari, M Shidqi; Maisa Aqila, Michelle Abla; Pradita Anwar, Nabilah; Rahmadhani, Novan; Ananda Mulya, Rizka (Seminar Nasional Lahan Suboptimal, 2022)
Nabil H, Wardhani A, Ghifari MSA, Aqila MAM, Anwar NP, Rahmadhani N, Mulya RA. 2022. The identification of fruit flies (Diptera : Tephritidae) on chili, guava, and bitter gourd in North Indralaya District, South Sumatera. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-10 Tahun 2022, Palembang 27 Oktober 2022. pp. 580-588. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).The invasion of fruit flies frequently found and causing crop failure to reduction of farm products. This paper aimed to find out the morphology of fruit flies which attacked on chili, guava, and bitter gourd in North Indralaya District, South Sumatera, Indonesia. This observation conducted on chili, guava, and bitter gourd in North Indralaya District, South Sumatera, Indonesia by sampling method that taken by attractan trap which contain metil eugenol as active material. The result showed that found four species of fruit flies which attacked on chili, guava, and bitter gourd in North Indralaya Disctrict, South Sumatera, Indonesia that is B. carambolae, B. dorsalis, B. umbrosa, and B. papayae. The Fruit fly B. papayae only found in guava while three others found in every observed plant. All of fruit flies has different morphology, such as colors, thorax, and abdomen. B. umbrosa's wings was easiest to identify than three others because it has three transverse patterns. However, the most specific feature is the abdoment whom has in each species. Thus, there are several species of fruit flies that find in North Indralaya District as B. carambolae, B. umbrosa F., B. papayae, also B. dorsalis from various of corps like chili, guava, and bitter gourd. Hopefullness, farmers could resolve fruit flies's damage, one of them by using attractan trap.